Raba pisnih in internetnih virov ter elektronskih medijev pri pripravi dijakov na preverjanje znanja iz slovenščine - Hromin, Petra; Čagran, Branka (Revija za elementarno izobraževanje, 2015)
The Students’ Use of Written and Internet Sources and Electronic Media for Assessment in Slovene. The article presents the frequency of using written and online sources as well as of electronic media during preparation of secondary school students for in-class examinations in Slovene language and literature. Within the scope of the above mentioned aspects we have controlled the of age and type of secondary school programmes. In the first part of the article the concept of information and communication technology/multimedia, the concept of e-learning and the concept of student activity are defined. In the second half of the article I present the results of the research, which show the frequency of use of written and web sources as well as of electronic media. These results have shown that with the oral examination of knowledge of grammar and literature the use of the notebook is prevalent, while with the written examination of knowledge of grammar and literature the use of the course book is predominant. The frequency of use of World Wide Web sources and electronic media increases with age and according to the level of difficultness of education programme. Thus the use of the notebook is the most prevalent in vocational schools whereas the use of the course book is predominant at the level of technical gimnazija and general gimnazija programmes.
Keywords: reading sources; secondary schools; multimedia; knowledge assessment